MADURESE LANGUAGE ATTITUDE IN LANGUAGE LEARNING THROUGH COVID 19: A CASE STUDY IN HIGHER EDUCATION - Zumam, Wildona; Amiruddin, Mohammad (KABILAH : Journal of Social Community, 2022)
Abstract: The purpose of this study is to describe the madurese language attitude and its influence on language acquisition during COVID 19. This is a qualitative case study study. This study includes students from Madura University’s English Department. The purposive sampling approach is used to choose a sample. During COVID 19, students were observed and interviewed to collect data on madurese language attitudes and their influence on language acquisition. The study’s findings show that the COVID 19 outbreak has had an impact on madurese language attitudes, such as the empathy level of 28 (50.9%) students; they have insufficient exposure and adaptability, and 21 (38.2%) students feel that the main point of COVID 19 effect is the students’ personalities. The COVID 19 pandemic has an impact on the empathy and personalities of university students. It makes pupils anxious when studying English and inactive when learning the language. It implies that, during COVID 19, teachers and academic society members should provide students with an appropriate language environment in order to create the right classroom conditions for students to receive meaningful input as well as social interaction in order to raise students’ awareness of their society. Members of academic organizations are urged to be responsive in order to provide useful feedback to students and to interact in a natural manner on a regular basis. Key words: Madurese, Attitude, Learning, Higher Education, COVID 19